To solve the equations \(-3x + 7 = 10\) and \(3x - 9 = 0\), let's solve each equation step by step.
1. Solving \(-3x + 7 = 10\):
\[ -3x + 7 = 10 \]
Subtract 7 from both sides:
\[ -3x = 10 - 7 \]
\[ -3x = 3 \]
Now, divide both sides by -3:
\[ x = \frac{3}{-3} \]
\[ x = -1 \]
2. Solving \(3x - 9 = 0\):
\[ 3x - 9 = 0 \]
Add 9 to both sides:
\[ 3x = 9 \]
Now, divide both sides by 3:
\[ x = \frac{9}{3} \]
\[ x = 3 \]
Final Solutions:
- From the first equation, \(x = -1\).
- From the second equation, \(x = 3\).
Thus, the solutions are \(x = -1\) and \(x = 3\).